Spaces of measures and their applications to structured population models - Düll, Christian; Gwiazda, Piotr; Marciniak-Czochra, Anna; Skrzeczkowski, Jakub (Cambridge monographs on applied and computational mathematics, 2022)
Analytical setting -- Structured population models on state space R -- Structured population models on proper spaces -- Numerical methods for structured population models -- Recent developments and future perspectives.